CRISPR/Cas9-Mediated Editing of OsPYL9 Enhances Drought Tolerance in Rice (Oryza sativa L.) through ABA and Circadian Rhythm Signaling - Sharif, Gulzaib; Yousaf, Rimsha; Kanwal, Attiya (INDONESIAN JOURNAL OF SUSTAINABILITY, 2026)
AbstractRice (Oryza sativa L.) is a major staple crop worldwide, yet its productivity is severely constrained by increasing drought stress driven by climate change and water scarcity. Abscisic acid (ABA) signaling plays a central role in regulating plant responses to drought, with the PYR/PYL/RCAR family of ABA receptors acting as key molecular regulators. Among these, OsPYL9 has emerged as an important candidate gene due to its involvement in drought tolerance and circadian rhythm–associated stress regulation. This study aims to enhance drought resilience in rice through precise genome editing of OsPYL9 using CRISPR/Cas9 technology. A locally adapted, high-yielding rice variety will be subjected to targeted gene modification, followed by molecular validation, physiological screening under controlled drought stress, and comprehensive agronomic evaluation. The expected outcomes include improved water-use efficiency, enhanced antioxidant activity, optimized stomatal regulation, and stable grain yield under water-limited conditions. This research provides a sustainable and precise breeding strategy for developing climate-resilient rice varieties and offers significant potential for strengthening food security in drought-prone regions.Keywords: CRISPR/Cas9, OsPYL9, Drought tolerance, Abscisic acid signaling, Rice genomics